Impact of the Coronavirus Disease Pandemic on Mental Health Among School Students in Korea During the COVID-19 Pandemic - Jang, Youngsoo; Cho, Hye-mi; Mok, Young-Eun; Chi, Su-hyuk; Han, Changsu; Yi, Hyun-suk; Lee, Moon-Soo (Journal of korean Academy of Child and Adolescent Psychiatry, 2023)
The coronavirus disease (COVID-19) pandemic has had various effects on mankind, especially children and adolescents. Because children and adolescents spend a lot of time at school, COVID-19 has had a great impact on school mental health. In this study, we investigated the effect of prolonged COVID-19 on school mental health. We prepared self-report questionnaires for depression (Children's Depression Inventory, CDI), anxiety (Korean version of the Penn State Worry Questionnaire for Children; Generalized Anxiety Disorder-7, GAD-7), and post-traumatic stress (Primary Care Post-traumatic Stress Disorder, PC-PTSD) for administering to students aged between 7 and 18 years, recruited by a COVID-19 psychological prevention support group in the Gwangmyeong Mental Health Welfare Center for 2 years, in 2020 and 2021. For children aged 7-12 years, there was no significant difference between the years 2020 and 2021 in the assessment of depression, anxiety, and post-traumatic stress. Conversely, for adolescents aged 13-18 years, there was a significant increase in the scale scores (CDI, PC-PTSD, and GAD-7). Prolonged COVID-19 might have had a significant impact on the mental health of adolescents who spent a lot of time at school. When comparing the years 2020 and 2021, middle and high school students were more affected by COVID-19 than elementary school students.